Java For Kids Solution for Preserving Javanese Culture for Elementary School Students - Delawanti Chrisyarani, Denna; Sesanti, Nyamik Rahayu (Jurnal Mitrawarga, 2024)
In the 21st century, the use of the Javanese language is decreasing. As a form of cultural preservation in education, it is transferred to Javanese language subjects. The Java For Kids program is a program that aims to help students learn Javanese language as it is applied in everyday life. The methods used in this service are lectures, demonstrations, assignments. This research was conducted at SDN Pandanmulyo 1 and 2 Tajinan, Malang Regency in class V. The results of the activities carried out went well in terms of attendance, student participation, material presentation, evaluation and reflection carried out by the service team. Judging from the evaluation results, it was also found that student scores had increased. Through this service activity, it is hoped that we can improve and provide strengthening of other materials related to the Javanese language so that local culture remains maintained and sustainable.